1940
DOI: 10.1172/jci101124
|View full text |Cite
|
Sign up to set email alerts
|

The Antistreptolysin Titer in Rheumatic Fever, Arthritis and Other Diseases

Abstract: Since 1933 a number of serologic tests have been made in the study of patients with rheumatic fever, arthritis, and several other diseases, who have come under the authors' care. These tests include gonococcus complement fixation, hemolytic streptococcus agglutinin and precipitin tests, and antifibrinolysin and antistreptolysin titrations. A preliminary report of the results of these was made in 1936 (1). The purpose of the present report is to give a more detailed analysis of the results of antistreptolysin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1942
1942
1965
1965

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…A similar observation in relation to antistreptolysin titers was made by Bunim and McEwen in 1940 (9 3. The mean antihyaluronidase titer for patients with active rheumatic fever was significantly higher than in any other group of patients studied.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A similar observation in relation to antistreptolysin titers was made by Bunim and McEwen in 1940 (9 3. The mean antihyaluronidase titer for patients with active rheumatic fever was significantly higher than in any other group of patients studied.…”
Section: Discussionsupporting
confidence: 77%
“…Antibodies against streptolysin "O" are formed in response to infection with the hemolytic streptococcus and for this reason measurement of antistreptolysin "O" has proved a useful test for indicating recent infection with the hemolytic streptococcus. Among the earlier important investigations of the antistreptolysin "O" titer in patients with hemolytic streptococcal infection, rheumatic fever and glomerulonephritis were those of (3), Myers and Keefer (1934) (4), Blair Fellow, 1947Fellow, -1949 and Pauli (1935) (7), Longcope (1936) (8), Bunim and McEwen (1940) (9), Windblad (1941) (10), and Mote and Jones (1941) (11). More recent studies have confirmed these earlier observations that the antistreptolysin "O" titer increases significantly following hemolytic streptococcal infections of the upper respiratory tract and during rheumatic fever.…”
Section: Historicalmentioning
confidence: 99%
“…Although, as was previously indicated, there was a higher incidence of the greater rises in antistreptolysin titer among the younger patients than among the older groups, the height of the rise depended on the presence or absence of edema, as well as on the age distribution. This is illustrated in Table V (8) found "no strict correlation between the age of the patient, the severity of the chorea, and the height of the antistreptolysin titer." Mote and Jones (6) found that the incidence of rises in antistreptolysin titer was greater in younger "healthy" control subjects than in the older age groups, presumably because of "a higher incidence of very mild or subclinical respiratory infections in children."…”
Section: Summary Of Materialsmentioning
confidence: 97%
“…The explanation for this apparent correlation between the magnitude of the antistreptolysin titer response and the occurrence of exacerbations in chronic glomerulonephritis is not clear from the data at hand. However, several possibilities may be considered, all of which have been mentioned by several authors (7,8,9,10,11,12,13) in discussions of the relation of the serum antistreptolysin titer to various diseases due to or associated with the group A hemolytic streptococcus. For example, certain strains of hemolytic streptococci may be more prone to evoke both exacerbations and larger rises in titer than other strains, although there is no direct evidence to support this possibility.…”
Section: Relation Of the Onset Of Antistreptolysin Titer Rise To The mentioning
confidence: 99%